2001
DOI: 10.1042/0264-6021:3570017
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular distribution of glycogen synthase and glycogen in primary cultured rat hepatocytes

Abstract: Changes in the intracellular distribution of liver glycogen synthase (GS) might constitute a new regulatory mechanism for the activity of this enzyme at cellular level. Our previous studies indicated that incubation of isolated hepatocytes with glucose activated GS and resulted in its translocation from a homogeneous cytosolic distribution to the cell periphery. These studies also suggested a relationship with insoluble elements of the cytoskeleton, in particular actin. Here we show the translocation of GS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 24 publications
(1 reference statement)
7
42
0
Order By: Relevance
“…Immunofluorescence analysis, using an antibody that specifically recognizes liver GS (6), showed that incubation with DHA produced an accumulation of the enzyme at the periphery of the hepatocytes, similar to that observed after glucose treatment. In control cells, GS was distributed throughout the cytoplasm, and, after incubation with glucose or DHA, the enzyme formed patches near the hepatocyte plasma membrane ( Fig.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Immunofluorescence analysis, using an antibody that specifically recognizes liver GS (6), showed that incubation with DHA produced an accumulation of the enzyme at the periphery of the hepatocytes, similar to that observed after glucose treatment. In control cells, GS was distributed throughout the cytoplasm, and, after incubation with glucose or DHA, the enzyme formed patches near the hepatocyte plasma membrane ( Fig.…”
Section: Resultsmentioning
confidence: 97%
“…First, the mere activation of GS induced by treatment with lithium chloride, a known inhibitor of glycogen synthase kinase-3 (42,43), is not sufficient to cause GS translocation to the hepatocyte periphery (6). Second, the common metabolites in the biosynthetic pathway of glycogen from glucose and from gluconeogenic precursors are Glc-6-P, which is in equilibrium with Glc-1-P, and UDP-Glc, the substrate of GS and immediate precursor in glycogen synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MGS is also concentrated in the nucleus at low glucose and translocates to the cytosol, where it adopts a particulate pattern, at high glucose concentrations (5,14). In contrast, LGS presents a cytosolic distribution in the absence of glucose and concentrates at the periphery of the hepatocyte when the concentration of the hexose increases (27). Finally HK I has been shown to reversibly bind to the outer mitochondrial membrane through a hydrophobic Nterminal sequence (28).…”
Section: Discussionmentioning
confidence: 99%
“…Protein was quantified using the Bradford assay (Bio-Rad, Hercules, CA, USA). Proteins were separated in a 10% SDS-PAGE gel, transferred to a PVDF membrane, and immunoblotted with rabbit anti-GS 3893 (1:1,000, Cell Signaling, Danvers, MA, USA), rabbit anti-muscle GS MGS3 [23], rabbit anti-liver GS L1 [24], mouse anti-actin AC-40 (1:25,000, Abcam, Cambridge, UK) and horseradish peroxidase-linked (anti-rabbit from GE, Little Chalfont, UK and anti-mouse from Dako, Glostrup, Denmark) secondary antibodies. Antibodies were validated using tissue/cell protein extracts where the antigen in question is not expressed.…”
Section: Methodsmentioning
confidence: 99%